A Dedicated Diversity Course or an Infusion Model? Exploring Which Strategy Is More Effective in Social Work Pedagogy. (2nd January 2018) - Pitner, Ronald O.; Priester, Mary Ann; Lackey, Richard; Duvall, Deborah
ABSTRACT: The Council on Social Work Education requires schools of social work to meet diversity and social justice competencies. Many MSW programs meet these standards by having either a dedicated diversity and social justice course, or by using some form of diversity and social justice curricular infusion. The current study explored which of these strategies is more effective. Two-hundred and eighty-six MSW students participated in this quasi-experimental design (diversity-83; infusion-97; no diversity/no infusion-106), and were assessed on multiple indices of cultural responsiveness and social justice awareness. Our findings were mixed, but indicated that a dedicated diversity and social justice course is effective at increasing students' cultural responsiveness and social justice awareness. Implications for social work pedagogy are discussed.